Produção de biomassa por fungos Filamentosos em meio de vinhaça de cana-de-açúcar suplementado com melaço - Silveira Ruegger, Marcelo José [UNESP]; Tauk-Tornisielo, Sâmia Maria [UNESP] (My University, 1996)
Three species of filamentous fungi, Aspergillus niger, Penicillium fellutanum and Mucor hiemalis, were selected and cultivated in vinasse media with different addition of molasses, pasteurized to 85°C for 30 minutes and with pH = 5.0. The microorganisms, previously adapted to the respective medium for 48 hours, from a solution of 107 spores.ml-1, were cultivated in pure and mixed cultures in Erlenmeyer vessel of 500ml, to 30°C, with constant agitation of 170 rpm, for 24, 48 and 72 hours, with four repetition for each samples. The biomass was separated by vacuum filtration in filter Whatman #1 and dried in oven at 105°C until right weight, the obtained liquid was submited to COD analysis. The datas were statistically analysed using a response surface methodology, to improve the effect on the molasses proportion and culture time, in the biomass production by microorganism in research. According to the obtained results (5.02% of molasses, 55.59h, 70% of spores solution of A. niger and 30% of spores solution of P. fellutanum), cultivating was carried out in Microferm Fermentor New Brunswick for 48 hours at 300 rpm, aired at 1v/v/m, using 5 liters of medium added with 5.0% of molasses on the conditions above described. The average of the results obtained (6.81g.l-1) was higher than the confidence interval (5.937 ; 6.369) and was inside the prediction interval (4.471 ; 7.834) both of them significant at 95% by the statistical test employed.
Biomass production by Filamentous fungi in sugar cane vinasse medium supplemented with molasses
Keywords: Biomass production; Mixed cultures; Vinasse